2013
DOI: 10.1016/j.jtcvs.2012.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative changes in cerebral oxygen metabolism following neonatal cardiac surgery: Effects of surgical duration

Abstract: Objective The early postoperative period following neonatal cardiac surgery is a time of increased risk for brain injury, yet the mechanisms underlying this risk are unknown. To understand these risks more completely, we quantified changes in postoperative cerebral metabolic rate of oxygen (CMRO2), oxygen extraction fraction (OEF), and cerebral blood flow (CBF) compared with preoperative levels by using noninvasive optical modalities. Methods Diffuse optical spectroscopy and diffuse correlation spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 25 publications
3
51
0
Order By: Relevance
“…The median (interquartile range) MRI-measured baseline OEF, S v O 2, CBF and CMRO 2 as well as DOS/DCS-measured baseline OEF, StO 2, BFI, CBV and CMRO 2i in the cohort are reported in Table 2 (StO 2 values in 14 babies from the present cohort were published previously in conjunction with a study evaluating postoperative changes in near-infrared spectroscopy parameters 16 ). Note substantial variation across subjects was observed among all measured resting-state variables.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median (interquartile range) MRI-measured baseline OEF, S v O 2, CBF and CMRO 2 as well as DOS/DCS-measured baseline OEF, StO 2, BFI, CBV and CMRO 2i in the cohort are reported in Table 2 (StO 2 values in 14 babies from the present cohort were published previously in conjunction with a study evaluating postoperative changes in near-infrared spectroscopy parameters 16 ). Note substantial variation across subjects was observed among all measured resting-state variables.…”
Section: Resultsmentioning
confidence: 99%
“…The study protocol has been described previously 15,16 and the timeline is illustrated in Figure 1. Briefly, once the anesthetized and paralyzed patient was stabilized and baseline DOS measurements were made while obtaining vascular access, patients were brought to the MRI scanner where a second MRI-compatible, noninvasive optical probe was placed on the forehead for continuous DOS/ DCS monitoring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong linear correlations were also present in a study comparing measurements based on DOS and DCS to magnetic resonance imaging measurements of blood flow and oxygen saturation in the superior sagittal sinus [30]. The new method was employed to evaluate postoperative relative cerebral blood flow, FTOE and CMRO 2 in comparison with preoperative levels [29,30].…”
Section: Discussionmentioning
confidence: 89%
“…Buckley et al [26][27][28][29] reported results obtained with a new optical method for determination of cerebral oxygen metabolism and regional cerebral blood using near infrared light. The measurements are based on diffuse optical spectroscopy (DOS) for quantification of cerebral tissue oxygen saturation and diffuse correlation spectroscopy (DCS) for monitoring cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%